(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This paper investigates the role of artificial intelligence (AI) technologies in forecasting and identifying cardiovascular diseases at early stages. Given that heart conditions are among the primary causes of death globally, early and accurate diagnosis is essential to prevent life-threatening outcomes. AI-driven approaches—especially those utilizing machine learning and deep learning—offer powerful tools for analyzing extensive clinical datasets, revealing subtle risk indicators and predictive trends with remarkable precision. The article explores how AI is transforming cardiology by improving diagnostic accuracy, aiding clinicians in decision-making processes, and delivering tailored medical guidance. Furthermore, the study evaluates international applications of AI in healthcare, outlining its advantages, existing challenges, and the future direction of AI-driven predictive medicine. Overall, the paper underscores the rising impact of digital technologies in addressing cardiovascular health and advancing personalized preventive care.